2016
DOI: 10.14434//josotl.v16i5.19975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parallel Authentic Research-Based Courses in Human Biology on Student Experiences at Stanford University and the University of Gothenburg

Abstract: Under a previous grant (2005-08), researchers and teachers at Stanford University (SU) and the University of Gothenburg (GU) co-designed a ten-week interdisciplinary, research-based laboratory course in human biology to be taught online to undergraduate students. Essentials in the subject were taught during the first four weeks of this course. Subsequently, student groups at SU and GU developed their own research questions, conducted live-streamed experiments remotely, processed their unique data with support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are also some foreign researches on network courses. For example, a learning research center in US conducted evaluation research on a lot of network courses and indicated that network courses could well change students' learning attitude and satisfy their learning needs [8]. American Institute of Higher Education [9] evaluated network courses as per online learning quality standards, and found that network courses can indeed improve students' learning enthusiasm and students are also satisfied with network courses.…”
Section: State Of the Artmentioning
confidence: 99%
“…There are also some foreign researches on network courses. For example, a learning research center in US conducted evaluation research on a lot of network courses and indicated that network courses could well change students' learning attitude and satisfy their learning needs [8]. American Institute of Higher Education [9] evaluated network courses as per online learning quality standards, and found that network courses can indeed improve students' learning enthusiasm and students are also satisfied with network courses.…”
Section: State Of the Artmentioning
confidence: 99%
“…Blended learning supports the use of interactive multimedia and collaboration in education and training and has become the tool of choice in education [ 12 14 ]. One form of online courses aimed at unlimited participation and open access are the Massive Open Online Courses (MOOC) [ 6 , 9 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%